2018
DOI: 10.14233/ajchem.2018.21386
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Synthesis of Gold Nanoparticles without Heating Process

Abstract: Gold nanoparticles are widely applied as sensors because of their unique physical and chemical properties. They have a large surface area and a high volume ratio, good conductivity, great mechanical strength and high electrocatalytic activities [1]. Their properties are unique due to the existence of the surface plasmon resonance (SPR) caused by electron oscillations in the conduction band when interacting with the light. The SPR of the AuNPs depends on the size, shape and composition of the particle as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…This change was confirmed by UV-Vis spectroscopy, which revealed a decrease in the intensity of the original SPR 4); this new SPR peak is ascribable to His-AuNPs aggregation. In addition, nanoparticles aggregation caused color changing and SPR peak widening [23]. This result is consistent with other studies that using AuNPs with thymine as a capping agent which showed the formation of new SPR peak UV-Vis spectra at around 650 nm after Hg 2+ addition [20].…”
Section: Colorimetric Detection Mechanismsupporting
confidence: 91%
“…This change was confirmed by UV-Vis spectroscopy, which revealed a decrease in the intensity of the original SPR 4); this new SPR peak is ascribable to His-AuNPs aggregation. In addition, nanoparticles aggregation caused color changing and SPR peak widening [23]. This result is consistent with other studies that using AuNPs with thymine as a capping agent which showed the formation of new SPR peak UV-Vis spectra at around 650 nm after Hg 2+ addition [20].…”
Section: Colorimetric Detection Mechanismsupporting
confidence: 91%
“…Reactions occurred in the precursor solution immediately after the introduction of L-ascorbic acid at room temperature. Furthermore, size control in the synthesis of Au NPs has been reported in several studies [ 37 , 38 , 39 ]. The ascorbic acid selectively reduces the Au ions in the HAuCl 4 /AgNO 3 mixed solution to form Au NPs due to their higher reducing potential than the Ag ions.…”
Section: Resultsmentioning
confidence: 99%
“…Curve (b) and inset image (b) show that the addition of PABA for functionalization cannot change the absorbance peak position (434 nm) and brownish yellow solution color; instead, it just caused a small decrease in the absorption value, suggesting an interaction between AgNPs and PABA via -COOH, and -NH 2 groups, as reported earlier. 59,60 On mixing 0.5 mL of the as-formed AgNPs with 0.5 mL buffer solution (pH ¼ 9.4) in a 3 mL calibration tube followed by diluting the solution with double distilled water to the mark, the absorption peak decreased sharply, while its position remained at 474 nm, and the color of the solution changed to pale-yellow due to the dilution of the AgNPs solution (curve (c) and inset image (c)). Addition of the NO 2 À solution of a certain concentration to 0.5 mL of AgNPs was studied in the same manner as explained in the recommended procedure.…”
Section: Resultsmentioning
confidence: 99%